2018
DOI: 10.1016/j.chempr.2018.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Room-Temperature Methane Conversion by Graphene-Confined Single Iron Atoms

Abstract: Graphene-confined single Fe atoms, screened out from a series of 3d transition metals (Mn, Fe, Co, Ni, and Cu), were used as an efficient non-precious catalyst to directly convert methane to C1 oxygenated products at room temperature. The unique O-FeN 4 -O structure formed in graphene can readily activate the C-H bond of methane along a radical pathway with a low reaction energy barrier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
343
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 402 publications
(361 citation statements)
references
References 37 publications
15
343
0
3
Order By: Relevance
“…In addition to the electrocatalytic reactions mentioned above, SACs have also been reported to be used in other catalytic reactions, including NRR, WGSR, methane reforming, methanol steam reforming, CO oxidation, benzene oxidation, acetylene hydrogenation, and so on. Shan et al reported an atomically dispersed Rh on the zeolite (Rh/ZSM‐5) catalyst, which can convert methane into methanol or acetic acid in liquid phase mild oxidation at 150 °C.…”
Section: Recent Advances Of Densely Populated Sacs In Catalytic Applimentioning
confidence: 99%
“…In addition to the electrocatalytic reactions mentioned above, SACs have also been reported to be used in other catalytic reactions, including NRR, WGSR, methane reforming, methanol steam reforming, CO oxidation, benzene oxidation, acetylene hydrogenation, and so on. Shan et al reported an atomically dispersed Rh on the zeolite (Rh/ZSM‐5) catalyst, which can convert methane into methanol or acetic acid in liquid phase mild oxidation at 150 °C.…”
Section: Recent Advances Of Densely Populated Sacs In Catalytic Applimentioning
confidence: 99%
“…The adjacent carbon atoms of FeN 4 center were also reconstructed with the high energy, leading to the dispersed single Fe atoms embedded into the defects of graphene (FeN 4 /GN) (Figure e,f). The unsaturated Fe sites of FeN 4 /GN possess the unsaturated FeN bonds, which exhibit high activity in catalyzing the oxidation reaction such as the oxidation of benzene to phenol and methane to C1 oxygenated products at room temperature . Therefore, high energy ball milling synthesis is a promising strategy to fabricate a variety of atomic metal catalysts on graphene without any extra external energy supply.…”
Section: Fabrication Strategies and Characteristic Methods Of Sagmentioning
confidence: 99%
“…Moreover, the formation of the extraordinary OFeN 4 O structure improves the electrocatalytic activity of the CH bond for forming the methyl radical at a low reaction energy barrier of 0.79 eV. In addition, the OFeN 4 O active sites could break the CH bonds of methane and directly convert it into C1 oxygenated products at 25 °C in methane oxidation process . Therefore, with the increasing of time, the products are almost CH 3 OH and CH 3 OOH in the first 100 min and then HOCH 2 OOH and HCOOH (Figure e).…”
Section: Electrochemical Applications Of Sagmentioning
confidence: 98%
See 1 more Smart Citation
“…[66][67][68] Auch Heterogenkatalysatoren kçnnen Methan zu Methanol umwandeln, z. Erst kürzlich wurden ein kolloidaler PdAu-Katalysator, [74] trägerfixierte Rh-Katalysatoren [76] und ein Graphen-eingeschränkter Einzelatom-Fe-Katalysator [75] entwickelt, die CH 4 auch bei tiefen Te mperaturen wirkungsvoll zu Methanol umwandeln konnten. [72,73] Bei diesem Verfahren sind hohe Reaktionstemperaturen (400-800 K) und -drücke (20-70 bar) erforderlich, um vernünftige Methan-Umwandlungsgeschwindigkeiten zu erzielen.…”
Section: Aufsätzeunclassified